Temperature and petrophysical modelling of the Antarctic peninsula Earth crust deep horizons - Korchin, V. A.; Burthyi, P. A.; Karnaukhova, E. E. (Ukrainian Antarctic Journal, 2014)
New unique information about elastic-density characteristics of the Antarctic peninsula rocks, directed on a subsequent study separate areas of mainland outskirts of the Antarctic peninsula, perspective on an accumulation hydrocarbons, are presented. Comparing the results of experimental investigations of elastic characteristics of rocks of the district Akademician Vernadsky station and Ukrainian shield at high pressures and temperatures with deep seismic sounding data in the district of continental areas of some DSS profiles and using the petrophysical thermobaric modelling method, the prognosis estimations of rocks distributing with the depth are done and also possible temperature distributing are expected in the Earth’s crust of the Antarctic peninsula area.